Acquired melanocytic nevus eclipse. - Milano, A. (European Journal of Pediatric Dermatology, 2019)
Molluscum contagiosum can also arise on other skin lesions and in the past we reported cases of molluscum contagiosum occurring on eruptive lobular angioma, on Spitz nevus and inside a fibropapilloma. In the literature there are less than 10 reports of molluscum contagiosum arising on melanocytic nevus. However, the latter is usually congenital (2) or very large (1) and therefore perhaps present since birth, while ours was a 2 mm acquired nevus. It is questionable whether molluscum contagiosum or any surgical trauma can cause a transformation of the nevus, hence with an indecision on the usefulness or less to remove molluscum contagiosum or the nevus together with it. Since melanoma is almost non-existent in the prepubertal child and molluscum contagiosum on melanoma with consequent destruction of the latter has been reported (1) we decided to wait for the spontaneous resolution of the lesion.